Study Level Of Flood Hazard Batang Kuranji River Pauh Sub District - Riha, Nafilah; Hermon, Dedi; Juita, Erna (Pendidikan Geografi, 2013)
Batang Kuranji is river that cleave Padang city at Province West Sumatera. This river upper zone to about Bukit barisan between District Solok with Padang City to empty into an estuary in Samudera Hindia. High rainfall with human factor make happen change characteristic especially at upper zone cause batang Kuranji stream. This research was conducted with the aim of 1) determine the characteristics of land Batang Kuranji Pauh sub district 2) determine the level of flood hazard Batang Kuranji Pauh sub district 3) analyze the spatial distribution of flood hazard Watershed (DAS) Batang Kuranji Pauh sub district.Existing land units in the study area consists of 13 land units and samples taken in this study were all land units. Sampling technique is stratified random sampling is a sampling technique that captured Strata (levell) land units. Analysis of the data used is descriptive analysis in the form of tables of comparison between the characteristics of the land (land form, slope of land, damming of rivers, river meanders, the average slope of the watershed, land use, rainfall, soil texture and soil permeability) were analyzed using Paimin methods in Hermon (2012).The results showed that: 1) there are differences in the characteristics of the land Â (land form, slope of land, damming of river, river meanders, the average slope of the watershed, land use, rainfall, soil texture and soil permeability) of each area of research that could potentially trigger flooding, 2) High level of flood hazards present in the study area with the Land Force F1.Qal.I.pm.Al, F1.Qal.I.Sw.Al, F1.Qal.III.Kc.Lat, F2.Qf.I.Kc.Lat, F2.Qf.I.Pm.Al, F2.Qf.I.Pm.Lat, F2.Qf.I.SwAl, F2.Qf.III.Ht.And, Â V1.QTau.III.Pm.Lat, V1.QTauIII.Pm.Lat, The study area has a moderate flood level of hazard present in the study area with land units V1.QTau.III.Ht.Lat, V1.QTau.III.Pm.Al, V1.QTau.III.H.And. 3) The area of research that has a high level with a broad floods 486.58 ha. And a research area with moderate flood hazard level has an area of 998.391 ha.Â